Determinants of Motor Vehicle Taxpayer Compliance with Public Service Accountability as Moderator (Case Study on Motor Vehicle Taxpayers in Keerom Regency) - Kambuaya, Maylen K. P.; Sesa, Pascalina V. S.; Larasati, Rudiawie (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to test and empirically analyze the Determinants of Motor Vehicle Taxpayer Compliance with Public Service Accountability as Moderator with a Study on Motor Vehicle Taxpayers in Keerom Regency. The data collection method is by the survey method; data is collected from 100 respondents who are motor vehicle taxpayers in Keerom Regency. Data was analyzed using partial least square analysis using warpPLS software. The findings indicate that taxpayer compliance costs significantly influence compliance, while moral obligation, love of money, and tax understanding show no direct effect. Additionally, public service accountability moderates the relationship between compliance costs and tax understanding with compliance yet fails to moderate the impact of moral obligation and love of money, highlighting selective moderating roles within taxpayer compliance dynamics. This research enhances the literature on how taxpayer behaviour and knowledge affecting taxpayer compliance, and especially how public service accountability plays important role in moderating determinants of motor vehicle taxpayer compliance.   It also highlights the need for government efforts to strengthen transparency, efficiency, and fairness in vehicle tax payment services, thereby fostering higher trust and willingness to comply.